Genetic mapping of a dominant gene conferring resistance to cassava mosaic disease - Akano, A.O.; Dixon, Alfred G.O.; Mba, C; Barrera Sabogal, E.; Fregene, Martin A. (Springer, 2002)
Cassava mosaic disease (CMD) is the most-important disease of cassava (Manihot esculenta) in Africa, and is a potential threat to Latin American (LA) cassava production. Although this viral disease is still unknown in LA, its vector – the whitefly – has recently been found. The disease is best controlled through host-plant resistance, which was first found in third backcross derivatives of an interspecific cross between cassava and Manihot glaziovii, and is thought to be polygenic. Recently, high levels of resistance were also found in several Nigerian cassava landraces. Classical genetic analysis and molecular genetic-mapping of the landraces showed that a major dominant gene confers this resistance. Bulk segregant analysis (BSA) was used to quickly identify a simple sequence repeat (SSR) marker linked to the CMD-resistance gene. The marker, SSRY28, is located on linkage group R of the male-parent-derived molecular genetic map. The gene, designated as CMD2, is flanked by the SSR and RFLP marker GY1 at 9 and 8 cM, respectively. To our knowledge, this is the first report of qualitative virus resistance in cassava, and of molecular markers that tag CMD resistance in cassava. We discuss the use of markers linked to CMD2 for marker-assisted breeding of CMD resistance in Latin America and for increasing the cost-effectiveness of resistance breeding in Africa.